2020
DOI: 10.2147/idr.s234295
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serotype Distribution and Antibiotic Susceptibility of <em>Streptococcus pneumoniae</em> Isolates in Tehran, Iran: A Surveillance Study</p>

Abstract: Introduction: Encapsulated Streptococcus pneumoniae strains cause high morbidity and mortality, mainly in countries with no pneumococcal conjugate vaccines (PCVs) immunization program. This study investigated the epidemiological changes of S. pneumoniae isolates including serotype distribution and antimicrobial susceptibility in Tehran, Iran. Methods: A total of 80 S. pneumoniae samples were collected from patients admitted to Shariati hospital over two periods. Half of the isolates were collected . The antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Vaccination has been shown to be effective in reducing the rates of IPD associated with multiple drug resistance [4,5]. But, vaccination against the most common serotypes of S. pneumoniae using PCVs is not still included to the routine immunization program in the Iran and only recommended for high-risk groups [28]. The present study, in addition to others from Iran, shows that the PCV13 could cover the majority of the invasive pneumococcal isolates [19,20,28,29].…”
Section: Resultsmentioning
confidence: 66%
“…Vaccination has been shown to be effective in reducing the rates of IPD associated with multiple drug resistance [4,5]. But, vaccination against the most common serotypes of S. pneumoniae using PCVs is not still included to the routine immunization program in the Iran and only recommended for high-risk groups [28]. The present study, in addition to others from Iran, shows that the PCV13 could cover the majority of the invasive pneumococcal isolates [19,20,28,29].…”
Section: Resultsmentioning
confidence: 66%
“…According to a study in Northeast Iran, serotypes 23F, 19F, 19A, 1, 14, and serogroup 6A/B were the most common types among children with suspected meningitis (8). Serotypes 23F, 14, 3, 19, and 19A were reported as the most prevalent in children with invasive and non-invasive pneumococcal infections admitted to Shariati Hospital, Tehran (9). Moreover, in a study on clinical samples obtained from children with an invasive pneumococcal disease from several hospitals in Tehran, 23F, 19F, 19A, and 9V as the most common serotypes (10).…”
Section: Resultsmentioning
confidence: 98%
“…In most cases, resistance is due to point mutations in atpC, which encodes an ATPase protein subunit (14,17). The differentiation of S. pneumoniae from other related species is essential to choose the appropriate therapeutic strategies, due to the increasing resistance to penicillin and macrolides among pneumococcal and other closely-related species (6,18). We demonstrated that the emergence of optochin-resistant isolates could disrupt the efficiency of conventional tests in diagnosing S. pneumoniae infections.…”
Section: Discussionmentioning
confidence: 96%